Evaluation of malnutrition in patients undergoing major abdominal surgery using GLIM criteria and comparing CT and BIA for muscle mass measurement. (August 2022) - Wobith, Maria; Herbst, Christian; Lurz, Markus; Haberzettl, Delia; Fischer, Martin; Weimann, Arved
Summary: Background & aims: GLIM criteria have become a worldwide standard for diagnosing malnutrition. They emphasize the measurement of muscle mass but do not provide clear recommendations for the use of different diagnostic tools and cut-offs. Measurements of body composition by using computerized tomography (CT) and bioelectrical impedance analysis (BIA) are both easily accessible in hospitalized patients. However, there is sparse data regarding the comparison for GLIM diagnosis of malnutrition and its prognostic impact for postoperative outcome in patients undergoing major abdominal surgery for cancer. Methods: We retrospectively analysed 260 patients undergoing major abdominal surgery between January 2017 and December 2019. Patients were prospectively screened and assessed for malnutrition with Nutritional Risk Score (NRS) and Subjective Global assessment (SGA). Body composition was analysed with CT scan and BIA within 30 days before surgery. GLIM criteria were retrospectively determined referring to the Fat free Mass from BIA (FFMBIA ) and Muscle Mass from axial CT scan at lumbar level 3 (MMCT ). The prevalence of GLIM - malnutrition according to BIA and CT was evaluated. Multivariate logistic regression analysis was used to determine association between malnutrition and outcome parameters. ROC-curves specified sensitivity and specificity of the different tools and areas under the curve were calculated. Results: From 260 patients in total, 179 patients (68.8%) had a confirmed malnutrition according to MMCT, 178 patients (68.5%) were malnourished according to SGA (grade B or C), whereas 66 patients (25.4%) were diagnosed with malnutrition using FFMBIA . The risk for developing a complication was significant associated with both methods, FFMBIA (OR 2.116, 95% CI 1.185–3.778, p = 0.01) and MMCT (OR 2.028, 95% CI 1..188–3.463, p = 0.009). Sensitivity for the prediction of overall complications was: MMCT 76.3%, FFMBIA 31.9%, and SGA 73.3%; specificity: MMCT 40.0%, FFMBIA 81.6%, and SGA 36.8%. Conclusion: When using GLIM criteria, the method for measuring muscle mass is pivotal resulting in considerable differences in prevalence, sensitivity, and specificity. GLIM criteria are predictive for the risk of developing complications in patients undergoing major abdominal surgery. With the pre-existing cut-offs, BIA seems to diagnose patients at an more advanced stage of malnutrition and indicates an advanced deterioration of nutritional status.